2021
DOI: 10.20448/journal.509.2021.81.97.102
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Inclusive Education Practices for Children with Disabilities and Other Special Needs in Uganda

Abstract: This study aimed to assess the factors that influence the effective implementation of inclusive education, taking into consideration learners with disabilities and other special needs. The study objectives focused on the following key aspects that directly influence the implementation of inclusive education: inclusive policies, attitudes, perceptions, curriculum issues, and learning environment. The study adopted a case study design and employed qualitative approaches in sampling. Participants of the study (N=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Intolerance is mainly caused by personal stereotypes and a negative attitude to interpersonal evaluation. Tolerance is the result of a conscious decision and can be defined as the principle of human interaction with other people, as well as from the readiness to form one"s world so strongly and flexibly that it is open to interaction with others (Kuyini et al, 2020;Okech et al, 2021). The development of a teacher"s readiness for inclusive educational practice includes the following personal characteristics: a conscious choice of options for their professional behavior; the ability and willingness to select rational means and methods of self-development; the organization of a teacher"s activities in a team; the ability to move freely in the system of techniques and methods of pedagogical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Intolerance is mainly caused by personal stereotypes and a negative attitude to interpersonal evaluation. Tolerance is the result of a conscious decision and can be defined as the principle of human interaction with other people, as well as from the readiness to form one"s world so strongly and flexibly that it is open to interaction with others (Kuyini et al, 2020;Okech et al, 2021). The development of a teacher"s readiness for inclusive educational practice includes the following personal characteristics: a conscious choice of options for their professional behavior; the ability and willingness to select rational means and methods of self-development; the organization of a teacher"s activities in a team; the ability to move freely in the system of techniques and methods of pedagogical activity.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rusman, the learning evaluation is conducted to determine the quality of learning from the planning, implementation, and evaluation of learning outcomes (Okech et al, 2021). Meanwhile, Suharsini AK and Lia Yuliana explained that the evaluation is conducted at the end of each completion of the standard competence of all subjects (Manubey et al, 2021).…”
Section: Inclusive Learning Evaluationmentioning
confidence: 99%
“…Rusman explained that education evaluation is conducted to determine the quality of education based on planning, implementation, and assessment of the results of the education program itself (Okech et al, 2021). Furthermore, Suharsini AK and Lia Yuliana state that assessments of education or learning are conducted after each subject's competency standard completion (Manubey et al, 2021).…”
Section: A Introductionmentioning
confidence: 99%
“…At the end of their research, they concluded that depending on the density of non-native speakers, the degree of language diversity did not have a negative effect on students' language and math skills but worsened the social integration of non-native speakers. In their research, Okech et al (2021) aimed to evaluate the factors affecting the effective implementation of inclusive education, taking into account learners with disabilities and other special needs. His research has focused on the following key aspects that directly affect the implementation of inclusive education: inclusive policies, attitudes, perceptions, curriculum issues and the learning environment.…”
Section: Introductionmentioning
confidence: 99%